2004
DOI: 10.1002/ijc.20039
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human vascular endothelial cells proliferation by terbinafine

Abstract: We have demonstrated previously that terbinafine (TB), an oral antifungal agent used in the treatment of superficial mycosis, suppresses proliferation of various cultured human cancer cells in vitro and in vivo by inhibiting DNA synthesis and activating apoptosis. In our study, we further demonstrated that TB at a range of concentrations (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Previously, we showed that terbinafine at a range of concentrations (30 -120 Amol/L) dose dependently inhibited angiogenesis by suppressing the proliferation of HUVEC and capillary-like tube formation in vitro and sprouting angiogenesis in vivo (8). Here, we further showed that terbinafine (30 -120 Amol/L) dose dependently inhibited HUVEC adhesion and migration.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Previously, we showed that terbinafine at a range of concentrations (30 -120 Amol/L) dose dependently inhibited angiogenesis by suppressing the proliferation of HUVEC and capillary-like tube formation in vitro and sprouting angiogenesis in vivo (8). Here, we further showed that terbinafine (30 -120 Amol/L) dose dependently inhibited HUVEC adhesion and migration.…”
Section: Discussionmentioning
confidence: 52%
“…These findings suggest that inhibition of cell adhesion could contribute only partially to endothelial migration inhibition induced by terbinafine treatment. Moreover, our previous study showed that terbinafine at a concentration of 120 Amol/L did not cause any cell death in HUVEC (8), suggesting that the terbinafine-induced endothelial migration inhibition was not due to cytotoxicity.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations